The economic effects of improving investor rights in Portugal - Castro, Rui (2009)
The Portuguese economy has performed remarkably well since join- ing the EU in 1986. Output per worker grew at an annual rate of 2.25%. The relative price of investment has declined. Real investment has increased compared to output, in part fuelled by an increase in capital inflows. At the same time, resource allocation seems to have improved as well: firm-level data shows a significant decline in the dispersion of labor productivity and size across firms. This paper argues that improvements in outside investor rights that have taken place since Portugal joined the EU is a prime candidate to explain this set of facts.